Resistance Distances in Linear Polyacene Graphs - Wang, Dayong; Yang, Yujun (Frontiers in Physics, 2021)
The resistance distance between any two vertices of a connected graph is defined as the net effective resistance between them in the electrical network constructed from the graph by replacing each edge with a unit resistor. In this article, using electric network approach and combinatorial approach, we derive exact expression for resistance distances between any two vertices of polyacene graphs.